Three Essays on the Economics of Education - Filiasov, Sergei (My University, 2025)
This dissertation examines how institutional features of K–12 education—specifically assessment design, grading practices, and the length and structure of the curriculum—shape students’ long-term academic and economic outcomes. Using linked administrative data from British Columbia and Newfoundland and Labrador, the chapters employ quasi-experimental and semi-parametric methods to address three policy-relevant questions: (i) how low-stakes standardized tests influence long-term outcomes through system accountability and individual feedback mechanisms; (ii) how the gap between teacher-assigned marks and standardized, curriculum-based exam scores relates to later earnings and what this implies about grading practices; and (iii) how extending the duration and altering the structure of the high school curriculum affects adult labour market outcomes and through which channels. Chapter 1 examines the long-term consequences of British Columbia’s grade 4 Foundation Skills Assessment (FSA), a low-stakes standardized test that reports results on a three-point scale publicly at the school level and on a five-point scale privately to students and parents. Using a regression discontinuity design at reporting thresholds, the analysis finds modest positive effects for girls on later academic outcomes. Specifically, girls who narrowly fall below the lowest reading threshold on the public scale show improvements consistent with a “system accountability” effect, while those just below the top numeracy cut-off on the private scale show evidence of a “feedback effect.” No significant effects are found for boys. Chapter 2 investigates how teacher-assigned and blind curriculum-based system-wide exam marks in grade 12 English relate to long-run earnings. While both assessment types are predictive of later labour income, their relative informativeness varies by student language background and grading environment. The teacher–exam mark gap is positively associated with earnings for English-speaking students, particularly in social-skill-intensive occupations, and negatively associated for English-as-a-Second-Language (ESL) students. Exam marks are more predictive in ‘grade-inflating’ schools. These results underscore the complementary roles of teacher assessments and standardized exams and the institutional contexts that shape their predictive value. Chapter 3 evaluates the long-term economic impact of Newfoundland and Labrador’s 1983–84 high school reform, which extended secondary education from grade 11 to 12 by introducing new (pre-)vocational electives but not substantially changing the core academic curriculum. Using an instrumental variable (IV) design and Census data, the study finds earnings gains of 10–11% when individuals are in the early 30s, with effects persisting into their 50s. These gains are driven primarily by increased outmigration among men and occupational upgrading among women. The reform did not significantly affect graduation rates or postsecondary attainment, suggesting that added vocational content alone can yield substantial and lasting economic benefits.